Fine green fluorescent powder for display as well as preparation method and application of fine green fluorescent powder

The YAG:Ce,M green phosphor addresses the stability issues of MiniLED displays by providing efficient, thermally stable, and cost-effective green light emission, enhancing MiniLED display performance.

CN119120020APending Publication Date: 2024-12-13FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310691293.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing MiniLED full-color technologies face issues with the stability and thermal stability of inorganic phosphors, particularly green phosphors, which have large particle sizes and agglomeration, affecting their performance in displays.

Method used

A green phosphor based on YAG:Ce,M with a molecular formula Y3-x-yAl5O12:Ce x,M y, where Ce is a luminescent ion and M is selected from In3+, Sc3+, Gd3+, Yb3+, or Lu3+, and the average particle size is less than 1 micron, prepared using wet chemical or solid phase methods, ensuring good thermal stability and matching the blue light chip.

Benefits of technology

The YAG:Ce,M phosphor emits green light efficiently with a peak value of 500-530nm, has excellent thermal stability, and is well-suited for MiniLED displays, improving display quality and reliability with a low-cost, simple process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120020A_ABST
    Figure CN119120020A_ABST
Patent Text Reader

Abstract

The invention discloses fine green fluorescent powder for display as well as a preparation method and application of the fine green fluorescent powder. The preparation method of the green fluorescent powder is a wet chemical method and / or a solid-phase reaction method; the green fluorescent powder is YAG: Ce, M, the molecular formula of the green fluorescent powder is Y3-x-yAl5O12: Cex, My, Ce is a luminous ion and is a positive trivalent ion, and M is a positive trivalent ion and is a negative trivalent ion. M is selected from at least one of In < 3 + >, Sc < 3 + >, Gd < 3 + >, Yb < 3 + > and Lu < 3 + >; 0.0001 < = x < = 0.5, and 0 < y < 3. The fine green fluorescent powder prepared by the invention can realize better coating property on a Mini LED on one hand, and on the other hand, the fine green fluorescent powder is high in luminous efficiency, good in thermal stability, easy in emission spectrum regulation and control, well matched with a blue light chip, capable of improving the display effect and reliability of the Mini LED, and suitable for being used as a fluorescent material for display of the Mini LED and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a green fluorescent material, in particular to a fine green fluorescent powder for display based on yttrium aluminum garnet nanometers, and a preparation method and use thereof. Background Art

[0002] MiniLED display is considered to be a new generation of display technology and has become a new growth and explosion point in the LED industry. Compared with LCD, OLED and other display technologies, MiniLED devices have many advantages such as self-luminescence, high contrast, high resolution, high reliability, long life and low power consumption. It has great market application prospects in large-size TV wall displays, car head-up digital displays, smart watches, flexible screens and other fields. There are two solutions for MiniLED full-color technology, one is the RGB three-color chip process, and the other is blue light chip + quantum dots. The second solution has a small quantum dot particle size and good coating, but there are problems with insufficient stability and service life. The stability of inorganic phosphors is much higher than that of quantum dots. Whether it is light stability or thermal stability, the phosphors synthesized by traditional inorganic solid-phase reactions have a larger particle size and more serious agglomeration, which affects the actual use effects such as coating. Therefore, how to refine the particle size of inorganic phosphors while maintaining high light efficiency is an important way to improve the practical level of MiniLED full-color solutions.

[0003] Commonly used green phosphors, such as silicon-based oxynitride (Sr,Ba)2SiO4:Eu 2+ 、SiAlON:Eu 2+ , aluminate (Ce, Tb)MgAl 11 O 19 :Ce has high light conversion efficiency, but the luminescence is easily thermally quenched, has poor thermal stability, and the excitation spectrum cannot match the blue light chip well. The high price of the raw material lutetium limits the promotion and application of lutetium aluminum garnet LuAG. Therefore, it is of great significance to prepare low-cost fine green phosphors with thermal stability and matching the wavelength of blue light chips. Summary of the invention

[0004] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0005] A green phosphor, the green phosphor is YAG:Ce,M, and its molecular formula is Y 3-x-y Al5O 12 :Ce x ,M y ,in,

[0006] Ce is a luminescent ion, which is a positive trivalent ion;

[0007] M is selected from In 3+ Sc 3+, Gd 3+ , Yb 3+ 、Lu 3+ At least one of the following;

[0008] 0.0001≤x≤0.5, 0<y<3.

[0009] According to an embodiment of the present invention, 0.005≤x≤0.2, preferably 0.005≤x≤0.01, for example, 0.01, 0.05, 0.1, 0.15, 0.2.

[0010] According to an embodiment of the present invention, 1.0<y<3, preferably 2.0<y<3, for example, 1.5, 2, 2.5, 3.

[0011] According to an embodiment of the present invention, the green phosphor has a yttrium aluminum garnet base.

[0012] According to an embodiment of the present invention, the average particle size of the green phosphor is not greater than 1 micron, preferably the average particle size is not greater than 0.5 micron, for example, 0.1 micron, 0.2 micron, 0.3 micron, 0.4 micron, 0.5 micron, 0.6 micron, 0.7 micron, 0.8 micron, 0.9 micron.

[0013] According to an embodiment of the present invention, the green phosphor emits green light with a peak value of 500-530nm under the excitation of light with a peak value of 300-500nm. Exemplarily, the green phosphor emits green light with a peak value of 530nm under the excitation of 450nm.

[0014] According to the embodiment of the present invention, the green phosphor has good thermal stability of light emission.

[0015] The present invention also provides a method for preparing the green phosphor, wherein the preparation method is selected from a wet chemical method or a solid phase reaction method.

[0016] According to an embodiment of the present invention, the wet chemical method specifically comprises the following steps:

[0017] (A1) adding a precipitant to an aqueous solution containing a reaction raw material to generate a precipitate through a hydrothermal reaction;

[0018] (A2) Drying and reacting the precipitate obtained in step (A1) to obtain the green phosphor.

[0019] According to an embodiment of the present invention, the reaction raw materials include an aluminum source, a yttrium source, a cerium source, and a M source.

[0020] According to an embodiment of the present invention, the aluminum source is selected from aluminum oxide and aluminum nitrate.

[0021] According to an embodiment of the present invention, the yttrium source is yttrium oxide or yttrium nitrate.

[0022] According to an embodiment of the present invention, the cerium source is selected from at least one of cerium oxide and cerium nitrate.

[0023] According to an embodiment of the present invention, the M source is selected from at least one of oxides, nitrates, chlorides and sulfates of M.

[0024] According to an embodiment of the present invention, in step (A1), the reaction raw materials are selected from water-soluble substances, thereby obtaining an aqueous solution containing the reaction raw materials.

[0025] According to an embodiment of the present invention, the concentrations of yttrium, aluminum, cerium and M ions in the aqueous solution containing the raw materials are not specifically limited, as long as the aqueous solution can be obtained, for example, 0.005-0.5 mol / L.

[0026] According to an embodiment of the present invention, the precipitating agent is selected from urea.

[0027] According to an embodiment of the present invention, the precipitant is provided by a solution containing the precipitant, wherein the concentration of the precipitant is 0.005-0.5 mol / L, preferably 0.05-0.1 mol / L.

[0028] According to an embodiment of the present invention, a dispersant may also be added in step (A1).

[0029] According to an embodiment of the present invention, the dispersant is selected from ammonium sulfate.

[0030] According to an embodiment of the present invention, the added amount of the dispersant is 0-20% of the molar amount of yttrium ions, preferably 5-10%, for example 5%.

[0031] According to an embodiment of the present invention, in step (A1), the precipitate can be further obtained by suction filtration.

[0032] Preferably, the suction filtration specifically comprises: first washing with deionized water, and then washing with anhydrous ethanol.

[0033] According to an embodiment of the present invention, in step (A2), the drying conditions include: drying at a temperature of 100-200° C. for 2-6 hours. Preferably, the drying temperature is 110-130° C. for 3-5 hours.

[0034] According to an embodiment of the present invention, in step (A2), the dried product may be sieved, for example, through a 200-mesh sieve.

[0035] According to an embodiment of the present invention, in step (A2), the reaction comprises: reacting at a temperature of 900-1300° C. for 2-6 hours. Preferably, the reaction temperature is 1000-1200° C. for 2-4 hours.

[0036] According to an embodiment of the present invention, in step (A2), the heating rate of the reaction is 50-150°C / min, for example, 100°C / min.

[0037] According to an embodiment of the present invention, in step (A2), the temperature is optionally cooled after the reaction, and the cooling rate is 50-150°C / min, for example, 100°C / min.

[0038] According to an embodiment of the present invention, the solid phase reaction method specifically comprises the following steps:

[0039] (B1) mixing the reaction raw materials and the carbon source and then blending to obtain a mixture;

[0040] (B2) Subjecting the mixture obtained in step (B1) to a sintering reaction to obtain the green phosphor.

[0041] According to an embodiment of the present invention, the reaction raw materials have the meanings as described above, including an aluminum source, a yttrium source, a cerium source, and an M source.

[0042] According to an embodiment of the present invention, the carbon source is selected from at least one of graphene, carbon nanotubes, activated carbon, carbon black, and carbohydrates.

[0043] According to an embodiment of the present invention, in step (B1), the mixture further comprises a dispersant.

[0044] According to an embodiment of the present invention, the dispersant is selected from ammonium sulfate.

[0045] According to an embodiment of the present invention, the added amount of the dispersant is 0-10% of the molar amount of yttrium ions, preferably 5%-10%.

[0046] According to an embodiment of the present invention, in step (B1), the mixing comprises ball milling the mixture in an organic solvent for 12-36 hours, preferably 20-30 hours.

[0047] According to an embodiment of the present invention, the boiling point of the organic solvent does not exceed 100° C. under normal pressure.

[0048] According to an embodiment of the present invention, the amount of the organic solvent added is 5-100% of the total mass of the reaction raw materials, preferably 10-50%.

[0049] According to an embodiment of the present invention, the organic solvent is at least one of acetone, ether, petroleum ether and ethanol.

[0050] According to an embodiment of the present invention, in step (B2), a drying treatment is further performed before the sintering reaction.

[0051] According to an embodiment of the present invention, the drying treatment condition is: drying at a temperature of 100-500° C. for 2-6 hours. Preferably, the drying temperature is 300-400° C. for 3-5 hours.

[0052] According to an embodiment of the present invention, in step (B2), the product may be ground and / or sieved after drying, for example, through a 200-mesh sieve after grinding.

[0053] According to an embodiment of the present invention, in step (B2), the sintering reaction comprises: sintering reaction at a temperature of 1000-1800° C. for not less than 1 hour. Preferably, the sintering reaction temperature is 1200-1500° C., and the sintering reaction time is 2-3 hours.

[0054] According to an embodiment of the present invention, in the solid phase reaction method, the heating rate of the sintering reaction is 50-150° C. / min, for example, 100° C. / min.

[0055] According to an embodiment of the present invention, after the sintering reaction, the temperature is optionally cooled, and the cooling rate is 50-150° C. / min, for example, 100° C. / min.

[0056] The present invention also provides a green phosphor obtained by the above preparation method, and the green phosphor has the meaning as described above.

[0057] The present invention also provides uses of the green phosphor, such as use in MiniLED display.

[0058] Beneficial effects:

[0059] (1) The yttrium aluminum garnet-based (YAG:Ce,M) fine green phosphor prepared by the present invention emits green light with a peak value of 500-530nm under the excitation of light with a peak value of 300-500nm;

[0060] (2) The green phosphor prepared by the present invention has an average particle size of no more than 1 micron (for example, 0.1 micron), is nearly spherical, and has good coating properties;

[0061] (3) The method of the present invention has the advantages of extensive raw materials, simple process and low production cost;

[0062] (4) The green phosphor prepared by the present invention has good thermal stability of luminescence and is well matched with the blue light chip. It can be used as a display fluorescent material such as MiniLED to improve the display effect and reliability of MiniLED. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 is the XRD spectrum of the green phosphor in Example 1;

[0064] Figure 2 is the emission spectrum of the green phosphor in Example 1 (excitation wavelength 450nm);

[0065] Figure 3 is a SEM image of the green phosphor in Example 1;

[0066] Figure 4 This is a thermal quenching diagram of the green phosphor in Example 1;

[0067] Figure 5 The SEM image of the green phosphor in Example 3

[0068] Figure 6 This is the SEM image of commercial LuAG:Ce phosphor;

[0069] Figure 7 is a SEM image of the green phosphor in Comparative Example 1;

[0070] Figure 8 This is the SEM image of the green phosphor in Comparative Example 2. DETAILED DESCRIPTION

[0071] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0072] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0073] Example 1

[0074] Preparation of green phosphor by wet chemical method:

[0075] Y(NO3)3, Al(NO3)3, Ce(NO3)3, and Lu(NO3)3 were dissolved in deionized water to obtain four solutions, wherein the concentrations of yttrium, aluminum, cerium, and lutetium ions in each solution were 0.3 mol / L, 0.3 mol / L, 0.05 mol / L, and 0.1 mol / L, respectively. The four solutions were mixed according to the molar ratio of yttrium, aluminum, cerium, and lutetium metal ions of 1:5:0.01:1.99, and ammonium sulfate (5% of the total molar amount of yttrium ions and lutetium ions) and excess urea were added, and transferred to a hydrothermal kettle for reaction at 200°C for 12 hours. After completion, a white precipitate was obtained. It was filtered, washed twice with deionized water, washed twice with anhydrous ethanol, dried at 110°C for 4 hours, ground through a 200-mesh sieve, and then placed in a high-temperature furnace and calcined at 1200°C for 4 hours to obtain a pure phase green phosphor YAl5O 12 :Ce 0.01 ,Lu 1.99 (See Figure 1 ); Under the excitation of the blue light chip at 450nm, the phosphor emits green light with a peak wavelength of 530nm (see Figure 2 ); average particle size of about 0.10 microns (see Figure 3 ); the intensity changes with temperature, indicating that Example 1 has excellent thermal stability of luminescence (see Figure 4 ).

[0076] Example 2

[0077] Preparation of green phosphor by wet chemical method:

[0078] Y(NO3)3, Al(NO3)3, Ce(NO3)3, and Lu(NO3)3 were dissolved in deionized water to obtain four solutions, wherein the concentrations of yttrium, aluminum, cerium, and lutetium ions in each solution were 0.3 mol / L, 0.3 mol / L, 0.05 mol / L, and 0.1 mol / L, respectively. The four solutions were mixed at a molar ratio of yttrium, aluminum, cerium, and lutetium metal ions of 0.5:5:0.01:2.49, and ammonium sulfate (5% of the total molar amount of yttrium ions and lutetium ions) and excess urea were added, and transferred to a hydrothermal kettle to react at 200°C for 12 hours. After completion, a white precipitate was obtained. Filtered, washed twice with deionized water, washed twice with anhydrous ethanol, dried at 120°C for 4 hours, ground, passed through a 200-mesh sieve, and then placed in a high-temperature furnace and calcined at 1300°C for 4 hours to obtain a pure phase green phosphor Y 0.5 Al5O 12 :Ce 0.01 ,Lu 2.49 .

[0079] Example 3

[0080] Preparation of green phosphor by solid phase reaction method:

[0081] Using α-alumina (α-Al2O3), yttrium oxide (Y2O3), cerium oxide (CeO2), and lutetium oxide (Lu2O3) powders as raw materials, according to the molecular formula Y 0.999 Ce 0.001 Lu2Al5O 12 The above raw materials are accurately weighed in a stoichiometric ratio to obtain a mixture, the total weight of the mixture is 15g. Activated carbon is added to the mixture, the amount of activated carbon added is 5% of the molar amount of the Y element, and then ball milled in anhydrous ethanol as an organic solvent (the amount ratio of anhydrous ethanol to the mixture is 5%) for 24 hours, and dried in a muffle furnace at 500°C for 2-6 hours to obtain a solid powder, which is sieved through a 200-mesh sieve. After sieving, the solid powder is reacted and sintered at 1650°C in a graphite heating element high-temperature sintering furnace for 2 hours, and the heating rate during sintering is 100°C / min, to obtain a pure phase green phosphor Y 0.999 Ce 0.001 Lu2Al5O 12 , after grinding through a 200-mesh sieve, the average particle size is about 0.10 microns (see Figure 5 ).

[0082] It can be seen that the green phosphor prepared by the solid phase reaction method (Example 3) has comparable performance to the phosphor prepared by the wet chemical method (Example 1), such as having similar powder particle sizes, and the dispersibility of Example 3 is better.

[0083] Compared with commercial LuAG:Ce phosphors (see Figure 6 , average particle size is about 0.50 microns), the green phosphor prepared by the method of the present invention has a smaller particle size, and at the same time, the content of the expensive lutetium element in the phosphor is lower, and the overall cost performance is higher.

[0084] Comparative Example 1

[0085] According to the literature (Functional Materials, 2018, 49, 1167), silicon nitride powder, aluminum nitride, aluminum oxide and Eu3Si2 alloy powder were mixed evenly according to the proportion. The mixture was calcined under 0.9MPa nitrogen pressure for 8h. The optimal calcination temperature was 1800-1950℃. After cooling, the product was ground and crushed, and sieved and graded with a 120-mesh nylon sieve to obtain the green phosphor SiAlON:Eu 2+ The powder morphology is long columnar or short columnar (see Figure 7 ), with an average particle size greater than 10 microns.

[0086] It can be seen from Comparative Example 1 that the nearly spherical fine powder prepared by the method of the present invention has better coating properties than the product of Comparative Example 1.

[0087] Comparative Example 2

[0088] According to the literature (Functional Materials, 2021, 52, 3160), Lu2O3, CeO2, and Al2O3 were mixed evenly according to the ratio, ground with anhydrous ethanol as the medium for 1 hour, and the mixture was ineffective. The mixture was transferred into a corundum crucible and calcined at 1500℃ for 3 hours in a muffle furnace under a reducing atmosphere (95% N2+5% H2). After cooling, the green phosphor Lu3Al5O 12 :Ce 3+ The powder morphology is amorphous, and the average particle size is about 3 microns (see Figure 8 ).

[0089] It can be seen from Comparative Example 2 that the green phosphor prepared by co-doping Y and Lu using the method of the present invention has a better morphology and a smaller particle size. Compared with the single Lu doping in Comparative Example 2, it can inhibit grain growth and the product has better coating properties.

[0090] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing green phosphor, characterized in that: The preparation method is selected from a wet chemical method or a solid phase reaction method; The green phosphor is YAG:Ce,M, and its molecular formula is Y 3-x-y Al5O 12 :Ce x ,M y , wherein Ce is a luminescent ion, which is a positive trivalent ion; M is selected from In 3+ Sc 3+ , Gd 3+ , Yb 3+ 、Lu 3+ At least one of the following; 0.0001≤x≤0.5, 0<y<3.

2. The preparation method according to claim 1, characterized in that: The wet chemical method specifically comprises the following steps: (A1) adding a precipitant to an aqueous solution containing a reaction raw material to generate a precipitate through a hydrothermal reaction; (A2) Drying and reacting the precipitate obtained in step (A1) to obtain the green phosphor.

3. The preparation method according to claim 1 or 2, characterized in that: The reaction raw materials include aluminum source, yttrium source, cerium source and M source. Preferably, the aluminum source is selected from aluminum oxide and aluminum nitrate. Preferably, the yttrium source is yttrium oxide or yttrium nitrate. Preferably, the cerium source is selected from at least one of cerium oxide and cerium nitrate. Preferably, the M source is selected from at least one of oxides, nitrates, chlorides and sulfates of M.

4. The preparation method according to any one of claims 1 to 3, characterized in that The precipitating agent is selected from urea. Preferably, the precipitant is provided by a solution containing the precipitant, wherein the concentration of the precipitant is 0.005-0.5 mol / L. Preferably, a dispersant is also added in step (A1). Preferably, the dispersant is selected from ammonium sulfate. Preferably, the added amount of the dispersant is 0-20% of the molar amount of yttrium ions. Preferably, in step (A2), the drying conditions include: drying at a temperature of 100-200° C. for 2-6 hours. Preferably, in step (A2), the reaction comprises: reacting at a temperature of 900-1300° C. for 2-6 hours.

5. The preparation method according to claim 1, characterized in that: The solid phase reaction method specifically comprises the following steps: (B1) mixing the reaction raw materials and the carbon source and then blending to obtain a mixture; (B2) Subjecting the mixture obtained in step (B1) to a sintering reaction to obtain the green phosphor.

6. The preparation method according to claim 5, characterized in that: The reaction raw materials include the aluminum source, yttrium source, cerium source and M source as described in claim 3. Preferably, the carbon source is selected from at least one of graphene, carbon nanotubes, activated carbon, carbon ink, and carbohydrates.

7. The preparation method according to claim 5 or 6, characterized in that: In step (B1), the mixture also includes a dispersant. Preferably, the dispersant is selected from ammonium sulfate. Preferably, the added amount of the dispersant is 0-10% of the molar amount of yttrium ions. Preferably, in step (B1), the mixing comprises ball milling the mixture in an organic solvent for 12-36 hours. Preferably, the boiling point of the organic solvent does not exceed 100° C. under normal pressure. Preferably, the amount of the organic solvent added is 5-100% of the total mass of the reaction raw materials. Preferably, the organic solvent is at least one of acetone, ether, petroleum ether and ethanol. Preferably, in step (B2), a drying treatment is performed before the sintering reaction. Preferably, the drying process is carried out at a temperature of 100-500° C. for 2-6 hours. Preferably, in step (B2), the sintering reaction comprises: sintering at a temperature of 1000-1800° C. for not less than 1 hour. Preferably, in the solid phase reaction method, the heating rate of the sintering reaction is 50-150° C. / min. Preferably, after the sintering reaction, the temperature is optionally cooled at a rate of 50-150° C. / min.

8. A green phosphor, characterized in that: The compound is obtained by the preparation method according to any one of claims 1 to 7.

9. The green phosphor according to claim 8, characterized in that: The green phosphor is YAG:Ce,M, and its molecular formula is Y 3-x-y Al5O 12 :Ce x ,M y , wherein Ce is a luminescent ion, which is a positive trivalent ion; M is selected from In 3 + Sc 3+ , Gd 3+ , Yb 3+ 、Lu 3+ At least one of the following; 0.0001≤x≤0.5, 0<y<3. Preferably, the green phosphor has a yttrium aluminum garnet base. Preferably, the particle size of the green phosphor is not greater than 1 micron. Preferably, the green phosphor emits green light with a peak value of 500-530nm under the excitation of light with a peak value of 300-500nm.

10. Use of the green phosphor according to claim 8 or 9.